1989
DOI: 10.1364/ao.28.005153
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optic pressure sensor on silicon substrate

Abstract: A novel integrated optic pressure sensor was constructed with the Mach-Zehnder interferometer structure of glass waveguides on a silicon substrate. Pressure is sensed by detecting the deformation of a thin diaphragm fabricated by using the anisotropic etching of a silicon substrate. The basic design concept of the present sensor was provided by analyzing its operation. The measurable pressure range and the sensitivity can be set by the proper selection of the diaphragm structure. A device was built and its ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…It has been shown that a membrane where the length/width ratio equals 2 will exhibit higher sensitivity [6]. Secondly, in [6] it is shown that using TM polarized light will enhance the sensitivity since the refractive index change in the out of plane direction is greater than it is in plane. Lastly, placing several membranes in series (as demonstrated by [3]) will also increase overall sensitivity of the device.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a membrane where the length/width ratio equals 2 will exhibit higher sensitivity [6]. Secondly, in [6] it is shown that using TM polarized light will enhance the sensitivity since the refractive index change in the out of plane direction is greater than it is in plane. Lastly, placing several membranes in series (as demonstrated by [3]) will also increase overall sensitivity of the device.…”
Section: Discussionmentioning
confidence: 99%
“…Thus light propagation in the rib region experiences a slightly larger effective index than that on the left and right sides of the rib, preventing the lateral spreading that normally occurs in planar waveguides [17,18,21]. The description of the fabricated rib waveguides dimensions are listed in Table 1.…”
Section: Waveguides Structurementioning
confidence: 99%
“…These characteristics make them extremely convenient as building blocks for devices such as sensors, lasers, amplifiers, directional couplers and others [17,18]. However, the production of high quality optical waveguides is not straightforward and, in particular, surface roughness constitutes a major concern [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Our group also has been developing silicon-based guided-wave optical pressure sensors, 7,8 microphones, accelerometers, 9 and flow sensors with diaphragms. These sensors have two unique features: guided-wave optical sensing and the use of micromechanical structures.…”
Section: Introductionmentioning
confidence: 99%